Consumers' Willingness to Pay (WTP) for Organically Farmed Fish in Bangladesh. (15th November 2021) - Hoque, Mohammed Ziaul; Akhter, Nazmoon; Mawa, Zinatul
Abstract: This study aims to assess the market potential for organically farmed shrimp. The rank-ordered logit model was employed to investigate consumer perceptions; the findings reveal that consumers prefer organic shrimp from mariculture, and inland-farmed shrimp to the coastal version. The willingness to pay (WTP) for conventional shrimp amongst consumers with low knowledge is less than that for organic shrimp amongst highly knowledgeable ones. In addition, the lower WTP for organic shrimp compared with safe shrimp amongst those with a medium knowledge level shows that the organically farmed shrimp market is lagging behind due to limited knowledge and confusion.